Hafez’s Gazelles as Seen by Farah Ossuli - Maleqi, Zahra (History and Culture, 2021)
The contemporary Iranian artist Farah Ossuli (born 1953), being inspired by classical Persian literature, has embodied in her oeuvre her own perception of a woman’s essence. Employing various techniques, she reflected in her canvases the work of poets coming from different eras, including Firdausi, Hafez, Nizami, Forugh Farrohzad, Sohrab Sepehri, and others.Our goal is, through analysis of some of the pictures, encouraged by Hafez’s gazelles (“The Birth of Venus”, “Dawn”, “Paradise”, “The Creation of Adam”, “Moon and Sun”, “Crossing the Sky”, “My Bird, Your Cage”), to define the commonalities of thoughts between a 21st century artist and a 14th century poet. During 4 years, Ossuli had created canvases inspired by 50 gazelles of Hafez, each of them drawing on one gazelle – in full, in part, or even on a single line.Hafez’s oeuvre contributed to the formation of Farah Ossuli’s own style in art. The outstandingly meaningful gazelles, created by the poet, facilitated the creation of no less meaningful and multifarious paintings, however, not always easily perceived by an ordinary spectator.
Keywords: Farah Ossuli; Hafez’s gazelles; “The Birth of Venus”; “Dawn”; “Paradise”; “The Creation of Adam”; “Moon and Sun”; “Crossing the Sky”; “My Bird, Your Cage”